Influenza B-associated acute myositis in a child in Sri Lanka: a case report - T. T. Pattiyakumbura; J. M. L. C. K. Jayasundara; P. B. U. S. Premarathne; S. Abeywardana; C. J. S. Jayamaha (Journal of Medical Case Reports)
Abstract Background Myositis, characterized by inflammation and weakness of skeletal muscles, is a multifactorial condition caused by various infectious, autoimmune, and neuromuscular disorders. Among these, infective myositis is a rare but significant clinical entity, predominantly caused by viral pathogens. Viruses such as influenza, enteroviruses, rubella, and human immunodeficiency virus are common culprits, with influenza-associated myositis being a particularly well-documented phenomenon. Despite its self-limiting nature in many cases, influenza-associated myositis warrants clinical attention owing to its potential complications and the diagnostic challenges it presents. Influenza B, a less antigenically variable subtype compared with influenza A, has been increasingly recognized as a cause of acute myositis, especially in pediatric populations. Case presentation We report the case of a 9-year-old Sri Lankan girl from central Sri Lanka who presented with a 4-day history of fever, cough, and cold, followed by bilateral calf pain and difficulty walking. On examination, she exhibited bilateral calf tenderness with normal muscle tone, power, and reflexes, without sensory impairment. Basic hematological investigations were within normal limits, but her creatine kinase levels were markedly elevated at 8370 U/L, indicating significant muscle damage. Ultrasound imaging revealed inflammation of the calf muscles. A nasopharyngeal swab tested positive for influenza B RNA, confirming the viral etiology. Supportive care resulted in complete symptom resolution within 10 days of hospital discharge. Conclusion Influenza-associated myositis is an important differential diagnosis for children presenting with muscle pain and gait disturbances during the influenza season. Early recognition and laboratory confirmation of the condition can prevent unnecessary investigations and facilitate prompt patient management. This case highlights the clinical and diagnostic aspects of influenza B-associated myositis, underscoring the importance of considering viral etiologies in pediatric patients with acute myositis.